Efisiensi Pemasaran Jagung Hibrida (zea mays L) di Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat - Sipayung, Jaja Parulian; Dang Sri Chaerani; Herda Gusvita (Fakultas Pertanian, Universitas Ekasakti, 2022)
This study aims to analyze the marketing channel and efficiency of hybrid corn in Luhak Nan Duo District, West Pasaman Regency. The selection of this location as the research area was carried out purposively with the consideration that the area is one of the centers for hybrid corn production in West Pasaman Regency. This research was carried out from March 20 to April 20, 2021. The research method used was descriptive qualitative method. and quantitative with a sample of 62 hybrid corn farmers. The data collected in the form of primary and secondary data. Data analysis was carried out descriptively qualitatively for data related to marketing channels and functions and descriptively quantitatively for analysis of marketing efficiency. The results obtained that 1). Based on the existing marketing channel pattern, the number of hybrid corn produced from Luhak Nan Duo District reached 483,000 kg and distributed to the final consumer, namely the animal feed factory in Payakumbuh through the I.a channel. Farmers – PPD - Factory CV. Ed Farm, channel I.b. Farmers – PPD – Factory UD. Rajawali, and Channel II. Farmers – PPD – PAD – Factory PT. King of Livestock Facilities. 2). Quantitatively, the efficient marketing channel is channel I.b where marketing margin is lower; farmer's share is higher, and the profit-to-cost ratio is smaller and the sales volume is larger.